Electric superbike racing: the design and construction of a championship winning electric superbike - Wheeler, Patrick; Blissett, Jonathan; Gimeno-Fabra, Miquel (2017)
The electric superbikes recently developed at The University of Nottingham have to be considered as a high performance vehicles, competing with its internal combustion engine driven counterparts. This paper presents the motivations for this work as well the design decisions taken to maximize performance in race conditions, along with modelling undertaken to gain an insight into the system interaction as a whole. Data recorded during races and on a rolling road are presented to validate the simulation work.